(3YLGdI GdHjGf aj TQM GdejRGfs - (3eMeO GdJGTcfOj,J (B980 (3g` s
(3ChdgG (B:s
(3fMeO Gddg HLejd CSeGFI CeG HYO agPg YLGdI GdHjGf ai TQM GdejRGf ddCSJGP GdCOj GddHjH YUGe GdOjf (B( (3GdESaQGjjfi (B) (3hHYO agPG ejRGf GdCOH ai dSGf GdYQH jMJed Cf jQjO HGdCOH ggfG Yde GdYQHjI s
(3BNQgG (B:s
(3hMSf GdcdGe Cf jJHY GddaX GdeYfi dG GdYcS , adGHO ef JQc GdJcdja dFdG jHdZ MO GdJYbjO ajNQL Yf fgL GdHdGZI , aEf GdMSf GdRGFO EfeG jYJHQ HYO JeGe GdCUd Je gPG GdcJGH HYhf Gddg Gdedc GdhgGH s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjf HGdeOGO GdCMeQs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1916s
Keywords: (3GddZIs